Color Image Encryption Using Hybrid Method of Fractal-Based Key and Private XOR Key - Faten H. MohammedSediq; Adnan Ibrahem Salih; Nevart A. Minas (Kirkuk Journal of Science, 2018)
The main idea of image encryption is to ensure secure transmitting it in the open network by transforming the image to not understandable form so that unauthorized person cannot decrypt and see it. This paper introduces a hybrid image encryption method based on the details of the Mandelbrot set fractals and the private XOR operation. Due to the random nature of fractal images, they can be used as a strong key for encryption. The strength of the key caused by using three random parameters as a secret keys (two of them are the zooming position values x & y, and the third is number of zooming times form that position) used to create the fractal-based key image, and they can generate large number of random fractal images. To make the secret image more secure, the original image is encrypted by applying XOR bit operation on each adjacent pixels of the image. At last the resulted image is combined with the previously obtained fractal-based key image using a predefined private XOR table in a complex order. To evaluate the performance of the system, the correlation coefficients, visual test using histogram analysis and different secret keys were used. All tested results proved that the proposed method is promising and effective to be used in image encryption fields.